Prototipe Sistem Informasi Reservasi Kos (Studi Kasus: Kos Wisma Cirebon Bandung - Nurismi Abdussamad; Leonardi Paris Hasugian (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2019)
The rapid development of information system today produce many innovations in the provision of services that provide services through information systems. Good service in a business greatly affects the increase or achievement of the efficacy of a business or service provider. Kos Wisma Cirebon is a provider of room rental services or boarding house located at Jl. Sekeloa Utara No.1, Sekeloa, Coblong, Bandung City, West Java, Indonesia. In managing boarding house activities there are several problems such as the process of finding information and reservations that require tenants to come directly so they have to spend more time and costs. Data management and archiving transaction data often accumulate and disappear resulting in frequent reporting errors. To manage some of these problems, the author tries to design a prototype boarding house reservation information system. In research conducted by the author using descriptive research methods. Data collection uses primary and secondary methods. The OOP system approach method uses UML as a tool, the prototype method as a system development method. The purpose of designing a prototype information system for boarding house reservation is to support the reservation process at Kos Wisma Cirebon. Can help minimize errors in making reports and assist in storing management data, as well as facilitate managers in boarding house management activities. Keyword : information systems, reservation, boarding house reservation information systems.